The Effect Of Income On Consumption In North Sumatra For The 2009-2021 Period: Pengaruh Pendapatan Terhadap Konsumsi di Sumatera Utara Periode 2009-2021 - Tasya Gabriella Sianturi; Nurita Pasaribu; Hotman Siboro; Rina Simamora (Outline Journal of Economic Studies, 2024)
This study aims to determine the effect of income on consumption in North Sumatra. The research method used is the integration between qualitative and quantitative methods. The data analysis technique used is in the form of multiple linear regression. The author conducted an empirical study with research objects in North Sumatra Province in 2009-2021. This research uses secondary data obtained from published data from the Central Statistics Agency (BPS) and the type of data used in this analysis is scaled data (time series). Data processing is carried out using the eviews 12 application by conducting a classic assumption test followed by a hypothesis test. The results of this study, partially the income variable affects the consumption variable. Simultaneously variable income.